LES PRINCIPALES CAUSES DES ACCIDENTS DE LA CIRCULATION ROUTIERE ET LES MESURES D’ATTENUATION EN ALGERIE - Madani Azzeddine; Tello Ghiat (European Scientific Journal, ESJ, 2015)
Algeria is ranked among the countries with a high number of traffic accidents, which causes several deaths and injuries each year. In this article we will put light on the causes of these accidents in the vast territory of Algeria which is located in Northen Africa and which has significant road infrastructures. We also intend to spread their distribution between urban and rural areas and their nature. We highlight the measures taken to reduce the number of such accidents , and to protect the lives of passengers and pedestrians by improving road networks safety inside and outside the cities. Finally we propose new measures to reduce accidents in highways and in different types of roads in Algeria.